Presencia de hidrocarburos fósiles en ecosistemas estuarinos del Golfo de México - Botello, Alfonso V. (Universidad de Costa Rica, 1978)
Samples of recent sediments and marine organisms (Crassostrea virginica and Thalassia testudinum), from seven coastal lagoons along the coast of the Gulf of Mexico, were analyzed to determine the actual levels of fossil hydrocarbons. The presence and identification of these hydrocarbons was determined by gas chromatography and gas cromatography-mass spectrometry. Results of this study show that the highest concentrations of fossil hydrocarbons were determined in organisms and sediments located near petrochemical complexes and oil refineries, indicating that petroleum hydrocarbons are being released into the coastal environment.